Epidemiology of musculoskeletal injuries in tennis players: risk factors - Minghelli, B.; Cadete, J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Tennis practice involves repetitive stresses through several strokes and movements during several hours. These factors can lead to injuries on musculoskeletal structures. This study aims to determine injury epidemiology in tennis players, as well as their type, location, mechanism of injury and risk factors. METHODS: The sample was constituted by 218 tennis athletes, aged 9 to 72, being 156 (71.6%) male. The measurement instrument was a questionnaire concerning characterization of the population, and aspects related to the modality and injuries. RESULTS: 86 athletes (39.4%) referred having an injury in a 12-month period, totalizing 107 injuries, and 76 athletes (34.9%) in a 6-month period, totalizing 95 injuries. There were 3.49 injuries per 1000 hours of tennis training. The most common injuries were joint injuries (29.5%), following by tendinopathy (22.1%), located in the ankle (20%) and wrist (15.8%), both occurred by service (23.2%). Tennis athletes who trained three times or more per week had 2.29 higher probability of injury (95% CI: 1.28-4.13; P=0.006), those who trained more than 4.5 hours per week had 2.04 more chances (95% CI: 1.16-3.60; P=0.013), those who were elite tennis players had 2.81 more chances (95% CI: 1.41-5.59; P=0.003), and those who trained on a clay court more frequently, had 4.11-fold higher probability of injury (95% CI: 1.46-11.55; P=0.007). CONCLUSIONS: In the analyzed sample, data revealed a high prevalence of injuries in tennis athletes, being joint injuries the most common type of injuries, and the most affected body area were the ankle and the wrist.